TRAUMA AS TRIGGER FACTOR AND MALNUTRITION STATUS AS RISK FACTOR IN THE ETIOPATHOGENESIS FOURNIER’S GANGRENE SCROTALIS ON A 39 YEARS OLD MAN - Habibi, Fajar Al (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Progressivity of the Fournier’s Gangrene (FG) is often fulminating and can rapidly cause multiple organ failure and death. Because of potential complications, it is important to diagnose the disease as early as possible. The purpose of this case report is to study how the role of the risk and trigger factors in the etiopathogenesis FG. A man, 39 years old, Body Mass Index (BMI) 17,77, came with a chief complaint of sudden pain in the scrotum accompanied by hot and discharging wound. Two days before hospital admission, patient suffered trauma to the lower abdomen. Patient complained of enlargement of the left scrotum. Scrotum feels hot and painful. The next day, the patient’s scrotum pus out. Physical examination found the left scrotum was bigger than the right one, and had an erosive ulcers with lot of discharge. The area is about ± 25 cm2. The layers of skin had necrosis at the wound area. Patient was diagnosed with FG clinically with Fournier’s Gangrene severity index (FGSI) 0-4. Patient was treated intravenous broad spectrum antibiotic ceftriaxon 2x1 gram per day and radical surgical debridement. Clinically, trauma are trigger factors while malnutrition status as a risk factor in the etiopathogenesis FG on this patient. [J Agromed Unila 2014; 1(3):263-267] Keywords: fournier’s gangrene, man, malnutrition, scrotum, trauma